Perception of natural habitat changes of West African marine protected areas - (:unkn) unknown (My University, 2020)
The evolution of marine protected areas (MPAs) in West Africa is reviewed through a survey of managers' perception carried on between 2017 and 2018 for the establishment of the baseline of MPAs of the Network of Marine Protected Areas of West Africa (RAMPAO). Managers report that all natural habitats are subject to surface area losses. The most affected habitats were beaches, mudflats and estuarine channels, caused by erosion and rainfall deficit. Seagrasses, rocky bottoms and coral reefs also seem to be affected, but as they are not monitored and as the managers' knowledge is poor toward these habitats, changes are not properly recorded. Despite some damages, coastal forests seem to be the only natural habitat that see positive changes, mainly due to regular reforestation activities. Comparing managers' perception to scientific papers using satellite imagery shows that their judgement is similar for some habitats (beaches and forests), although there are some differences between their perception and scientific analyses about mangroves changes and even between scientific analyses themselves. However, managers' understanding of impacts coming from human activity and climate change is not strong enough. Consequently, these threats
Keywords: African Research